Epidemiology of Post-Infarction Ventricular Septal Rupture in Patients Undergoing Surgical Repair at Different Times from the Development of Acute Myocardial Infarction - Ramil A. Aliyev; Yelizaveta O. Lebedieva; Mykhailo M. Grusha; Kamran K. Musayev (Ukrainian Journal of Cardiovascular Surgery, 2021)
Introduction. The article is dedicated to the epidemiological aspects of the mechanical complication of acute myocardial infarction (AMI), particularly post-infarction ventricular septal rupture (VSR), problematic issues of its etiology and localization. Mortality of such patients is determined by rapid development of hemodynamic disorders and their severity, unpredictable clinical course, and the difficulty of early diagnosis. In addition, the high mortality rate of patients, especially when correcting the ventricular septal defect at the early stages after AMI, leaves open the question of the tactics of surgical treatment. The influence of certain risk factors of ischemic heart disease (IHD) on the development of post-infarction VSR is also considered.The aim. To study the epidemic features of post-infarction VSR in patients with different terms of surgical intervention after the development of AMI.Materials and methods. This study presents a retrospective analysis of 90 patients with coronary artery disease complicated by post-infarction VSR, who underwent surgical intervention for the period 2002-2019. The ages of hospitalized patients with post-infarction VSR ranged from 29 to 81 years. All the patients were divided into 3 groups depending on the time interval from AMI to surgical intervention.Results and discussion. It was found that post-infarction VSR is more common in men in the age range of 45-74 years after the manifestation of the first transmural AMI. More than a half of post-infarction VSR cases (56.7%) are associated with anterior localization of the ruptures in consequence of anterior AMI. Since the leading role in the treatment of AMI belongs to percutaneous coronary interventions (PCI), we analyzed the use of various reperfusion techniques to restore coronary blood flow in patients with post-infarction VSR. The analysis suggests that there are no statistically significant differences between the studied groups of patients with post-infarction VSR who underwent myocardial reperfusion (p = 0.103).Conclusions. The presence of chronic renal failure (CRF) in patients in the early post-infarction period can complicate the course of post-infarction VSR and affect perihospital mortality. The absence or untimeliness of myocardial reperfusion increases the risk of developing this complication of AMI. The ambiguous prognosis of treatment of post-infarction VSR makes a serious problem for clinicians.